Are remittances a substitute for credit? Carrying the financial burden of health shocks in national and transnational households - Christian Ambrosius (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2012)
The assumption that remittances are a substitute for credit has been an implicit or explicit theoretical foundation of many empirical studies on remittances. This paper directly tests this assumption by comparing the response to health-related shocks among national and transnational households using panel data from Mexico for 2002 and 2005. While the occurrence of serious health shocks that required hospital treatment doubled the average debt burden of exposed households compared to the control group, households with nuclear family members (a parent, child, or spouse) in the US did not increase their debts due to health shocks. This finding is consistent with the view that remittances respond to households' demand for financing emergencies and make them less reliant on debt-financing.
Keywords: F24; D14; I15; O12; 330; Rücküberweisung (Migranten); Privater Haushalt; Krankheit; Schock; Finanzierung; Kredit; Private Verschuldung; Mexiko